Associations of human colorectal adenoma with serum biomarkers of body iron stores, inflammation and antioxidant protein thiols - Schöttker, Ben; Gao, Xin; Jansen, Eugène H. J. M.; Brenner, Hermann (Antioxidants, 2021)
Red and processed meat consumption and obesity are established risk factors for colorectal adenoma (CRA). Adverse changes in biomarkers of body iron stores (total serum iron, ferritin, transferrin and transferrin saturation), inflammation (high-sensitivity C-reactive protein [hs-CRP]) and anti-oxidative capacity (total of thiol groups (-S-H) of proteins [SHP]) might reflect underlying mechanisms that could explain the association of red/processed meat consumption and obesity with CRA. Overall, 100 CRA cases (including 71 advanced cases) and 100 CRA-free controls were frequency-matched on age and sex and were selected from a colonoscopy screening cohort. Odds ratios (OR) and 95% confidence intervals (95%CI) for comparisons of top and bottom biomarker tertiles were derived from multivariable logistic regression models. Ferritin levels were significantly positively associated with red/processed meat consumption and hs-CRP levels with obesity. SHP levels were significantly inversely associated with obesity. Transferrin saturation was strongly positively associated with overall and advanced CRA (ORs [95%CIs]: 3.05 [1.30-7.19] and 2.71 [1.03-7.13], respectively). Due to the high correlation with transferrin saturation, results for total serum iron concentration were similar (but not statistically significant). Furthermore, SHP concentration was significantly inversely associated with advanced CRA (OR [95%CI]: 0.29 [0.10-0.84]) but not with overall CRA (OR [95%CI]: 0.65 [0.27-1.56]). Ferritin, transferrin, and hs-CRP levels were not associated with CRA. High transferrin saturation as a sign of iron overload and a low SHP concentration as a sign of redox imbalance in obese patients might reflect underlying mechanisms that could in part explain the associations of iron overload and obesity with CRA.